Genetic Approaches to Reveal the Connectivity of Adult-Born Neurons - Arenkiel, Benjamin (Frontiers in Neuroscience, 2011)
Much has been learned about the environmental and molecular factors that influence the division, migration, and programmed cell death of adult-born neurons in the mammalian brain. However, detailed knowledge of the mechanisms that govern the formation and maintenance of functional circuit connectivity via adult neurogenesis remains elusive. Recent advances in genetic technologies now afford the ability to precisely target discrete brain tissues, neuronal subtypes, and even single neurons for vital reporter expression and controlled activity manipulations. Here, I review current viral tracing methods, heterologous receptor expression systems, and optogenetic technologies that hold promise towards elucidating the wiring diagrams and circuit properties of adult-born neurons.